CAMPUR KODE DALAM LIRIK LAGU BATAK TOBA - Netti Malini; Mangatur Sinaga; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study is a mixed language code study included in the lyrics of the Batak Toba song. This study aims to describe the mixed codes that are contained in the lyrics of the Batak Toba song and describes the types of code mix that are used in the lyrics of Batak Toba. To describe the mixed codes and codes in the lyrics of the Batak Toba song, mixed-code theory refers to Suwito's opinion (in Wijana 2012: 171) and Kridalaksana (2008: 41). The method used in this research is the descriptive method, ie the research that collects, processes and analyzes data at the time of the research. The conclusion of this study is to consist of code hybrids in Toba Batak lyrics contained by the form of the word, sentences, sections and form loops berebntuk are said. Mixed code in the form of words in the lyrics of Batak Toba Songs amounted to 21 dates. Mixed code in the form of phrases in the lyrics of Batak Toba Songs amounted to 17 dates. Mixed code in the form of clauses in the lyrics of Batak Toba Songs amounted to 7 dates. Mixed code in the form of repetition of words in the lyrics of Batak Toba Song amounted to 5 dates. The type of code mix used in the lyrics of the Batak Toba song is to mix code in (inner code mixing) and mix code-out (outer code mixing). Through this study, the authors suggest that more research is included in the code overlap in the lyrics Batak Toba.Keywords: Sosiolinguistics, Song Lyrics, Batak Toba.